The clinical utility and safety of short‐course immune checkpoint inhibitors in multiple tumours—A real‐world multicentric study from India. Issue 6 (25th November 2021) - Abraham, George; Noronha, Vanita; Rajappa, Senthil; Agarwal, Amit; Batra, Ullas; Somani, Naresh; Raja, Thirumalairaj; Patil, Shekhar; Kaushal, Ashish M.; Joshi, Ashish; Radhakrishnan, Vivek; Singh, Navneet; et al.
Abstract: The real‐world data on short course of immune checkpoint inhibitor (ICI) use are sparse and merit exploration. A multicentric observational study on the safety and efficacy of ICI in oncology patients between August 2014 and October 2020 involves 1011 patients across 13 centers in India. The median age was 59 (min 16‐max 98) years with male preponderance (77.9%). The predominant cohort received short‐course ICI therapy; the median number of cycles was 5 (95% confidence interval [CI] 1‐27), and the median duration of therapy was 3 (95% CI 0.5‐13) months. ICIs were used commonly in the second and third line setting in our study (66.4%, n = 671). Objective response rate (complete or partial response) was documented in 254 (25.1%) of the patients, 202 (20.0%) had stable disease, and 374 (37.0%) had progressive disease. The clinical benefit rate was present in 456 (45.1%). Among the patients whom ICI was stopped (n = 906), the most common reason for cessation of ICI was disease progression (616, 68.0%) followed by logistic reasons like financial constraints (234, 25.82%). With a median follow‐up of 14.1 (95% CI 12.9‐15.3) months, there were 616 events of progression and 443 events of death, and the median progression free survival and overall survival were 6.4 (95% CI 5.5‐7.3) and 13.6 (95% CI 11.6‐15.7) months, respectively, in the overall cohort. Among the immune‐related adverse events, autoimmune pneumonitis (29, 3.8%) and thyroiditis (24, 2.4%) were common. Real‐world multicentric Indian data predominantly with short‐course ICI therapy have comparable efficacy/safety to international literature with standard ICI therapy. Abstract : What's new? Immune checkpoint inhibitors (ICIs) are now a standard of care for many cancers. Unfortunately, their cost is still prohibitively high for many patients in low‐ and middle‐income countries (LMICs). Recently, however, lower overall dosages have shown considerable promise. But will this lower‐cost approach work for patients with diverse genetic backgrounds? In this large Indian study, the authors found that short‐course ICIs had similar efficacy and safety profiles in South Asian patients as those seen in other ethnicities and countries. This may thus encourage the use of ICIs in LMICs.